The Relationship Between Organisational Culture and IT Utilisation Using the Unified Theory of Acceptance and Use of Technology Among Credit Unions in Indonesia - Indra, Samsie (2024)
Much research has been conducted to study IT acceptance in organisations by considering organisational culture as a determining factor. This study became the first to use the Competitive Value Framework (CVF) and quadrant driving value as an antecedent for individual perception from Unified Theory Acceptance and Use Technology (UTAUT). Data was collected using a questionnaire. Data from two hundred eighty-eight respondents were analyzed using the SEM-PLS method and SMART-PLS4 software. The analysis uses the Reflective Formative Second Order Two-Stage Approach, where organisational culture (OC) variables are analyzed using formative methods. In contrast, the other variables are analyzed reflectively. The linear regression calculations are conducted for each OC dimension to each UTAUT individual's perceptions to see the relationship. The results have a significant relationship between OC and BI via EE and SI, while OC to BI via PE is insignificant. In linear regression, all dimensions affect PE; the dimensions that affect EE are clan and adhocracy, while those that affect SI are hierarchical, market, and adhocracy dimensions. From these results, OC can affect individual perceptions of wanting to use information technology. These results will contribute to theories about culture, especially organisational culture and information technology. The result proved that OC can be an antecedent of individual perception. In addition, using value drivers from each dimension becomes a valuable input for survey methodology. These findings help decision-makers pay more attention to value drivers in organisations if they want to implement new technologies to avoid employee rejection.